Symmetric Blind Decryption with Perfect Secrecy - Juha Partala (Journal of Computer Networks and Communications)
A blind decryption scheme enables a user to query decryptions from a decryption server without revealing information about the plain-text message. Such schemes are useful, for example, for the implementation of privacy-preserving encrypted file storages and payment systems. In terms of functionality, blind decryption is close to oblivious transfer. For noiseless channels, information-theoretically secure oblivious transfer is impossible. However, in this paper, we show that this is not the case for blind decryption. We formulate a definition of perfect secrecy of symmetric blind decryption for the following setting: at most one of the scheme participants is a passive adversary (honest-but-curious). We also devise a symmetric blind decryption scheme based on modular arithmetic on a ring Zp2, where p is a prime, and show that it satisfies our notion of perfect secrecy.